Concentration Exercises for Volleyball Players: A Systematic Review - Hidayat, Taufiq; Muhammad, Heryanto; Wibowo, Sapto; Wicahyani, Sri; Tazkiyah, Amalia; Abdil Khuddus, Lutfhi (Proceeding of International Joint Conference on UNESA, 2025)
The purpose of this study is to analyze research on the importance of concentration and concentration training in volleyball players. The research method used is a systematic review of journal articles and proceedings Google Scholar, Scopus, Web Of Science and PubMed databases. Researchers use a framework with inclusion criteria, namely concentration exercises for volleyball players, and exclusion criteria, namely articles published in non-reputable journals in fake journals. The results of this research are volleyball coaches and sports psychologists should encourage players to focus on the target areas that the coach has planned to improve player performance. Good concentration is essential in decision making on the court. In a matter of seconds, a player must evaluate the situation, determine the most appropriate action, and carry it out. This involves quickly processing visual and tactile information, such as the position of opponents and teammates. Players who are able to maintain focus are more likely to make strategic decisions that benefit the team, both in attack and defense.Forms of concentration training for volleyball players based on this study include attention training, drills with visualization and reaction training, mental training and meditation. In addition, adequate rest (sleep) is also an important factor in maintaining player concentration.